AN ANALYSIS OF THE HISTORY AND CONTENT OF THE CAIRO DECLARATION ON HUMAN RIGHTS IN ISLAM (The Conference Hub, 2025)
Human rights are one of the most important values and criteria of social development in modern society. The level of progress of any state is primarily determined by the respect it shows for human dignity and fundamental freedoms. The adoption of the Universal Declaration of Human Rights by the United Nations (UN) in 1948 marked a major step toward establishing universal human rights standards. In response, the Muslim world, based on its own religious and moral principles, adopted the Cairo Declaration on Human Rights in Islam in 1990.